The Influence Of Influencer Marketing On The Purchase Decision Of Ventela Brand Shoes With Brand Trust As A Mediation Variable And Brand Image As A Moderation Variable - Bagaskara, Rahadian Bintar; Prasetyo, Arya; Ardhana, Noval; Mozart, Mohammad (Growth: Journal Management and Business, 2024)
This study aims to analyze more deeply the Influence of Influencer Marketing on the Purchase Decision of Ventela Brand Shoes with Brand Trust as a Mediation Variable and Brand Image as a Moderation Variable. The research method used is quantitative by using primary data in the form of questionnaires. The sample used in this study was 100 respondents. Data processing is carried out using Smart-PLS 3. The results of this study show that influencer marketing has a positive effect on purchase decisions and subsequently influencer marketing has a positive effect on brand trust. Other findings show that brand image has a positive effect on purchase decisions and brand trust has a positive effect on purchase decisions.